SYNODALITY: TOWARD ECUMENISM AND INTER-RELIGIOUS DIALOGUE - Pandego, Higianes Indro; Suwartono, Yustinus (LOGOS, 2024)
Encounter, listen and discern! These three messages from Jesus are for spreading the gospel. He leads the Twelve and his followers in contact with the Holy Trinity and with humanity. The Church continued the Kingdom of God's mission to rule the globe. The synod is called upon by the authority of the Church to uphold and carry out the faith, moral doctrine, and disciplines of the Church. Additionally, the church moves forward in a synodal spirit. With churches and ecclesial communities, the Church fosters ecumenism. She also fosters interfaith dialogue with other religions. And the Basic Ecclesial Communities, which are preval_ent among the population, are the most significant element in this style of life.